Diagnóstico comunitario de salud del Barrio Florencia, septiembre-diciembre de 2013 - Jumbo Jumbo, Doris Carolina (2013)
The present investigation " DIAGNOSIS COMMUNITY HEALTH DISTRICT FLORENCE, SEPTEMBER- DECEMBER 2013 " aims to: Conduct community assessment of the influence area of the University Hospital of Motupe with their epidemiological profiles and talking maps, as a basis for the formulation Development Project in the health sector which sustainability proposed work health unit will be provided . Provide specific nursing services, designed to ensure the exercise of the right to health of disadvantaged groups as a form of community outreach and linking strategy with the health service. The study is descriptive in a universe of 164 inhabitants 89 women and 75 men, among the most important data stand out, the 83.44% of families contributed a 2.08% not found and 14.58% are vacant houses, among biological hazards are located on 3.05% of children and adolescents with nutrition problems in the health risks of unsafe water consumption at 100%, in socioeconomic risk poverty with 95%, 4.27% illiteracy was found, as concerning sexually active women the 84.61% use natural family planning method. Regarding the epidemiological profile is highlighted, chronic diseases and disabilities which allowed the update of the classification of catastrophic illnesses and disabilities. With the results obtained health teams to raise strategies aimed at improving the situation of the community, insisting that no families entered this study and then incorporate recommended. The information is consolidated, using tables and charts to reach the final lifting of talking map, which was supported by the physical map that was done throughout the day in the community. Keywords: Health Study, research Barrio "Florence", community, situational.